RELEVANSI SIFAT PENDIDIK MENURUT ABDULLAH NASHIH ULWAN MENGHADAPI TANTANGAN PENDIDIKAN DI ERA MASYARAKAT 5.0 - Razi Ghazali; Moh. Ali (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) STIT Muhammadiyah Tempurejo, Ngawi, Jawa Timur, 2025)
The aim of this research is to describe the importance of sincerity, piety, knowledge, patience and responsibility for educators as expressed by Abdullah Nashih Ulwan (Ulwan) in Tarbiyatul aulad fil Islam, as well as knowing its relevance to the challenges in education in the era of society 5.0. This research uses a descriptive qualitative approach with a library research method used to collect data through reference sources such as books, articles, journals, scientific papers related to the topic of discussion. The research results show that Ulwan values remain relevant as an ethical foundation in strengthening the qualities of educators, from the aspects of character, faith and knowledge amidst the dynamics of society 5.0 in the field of education. It is hoped that the values expressed by Ulwan can strengthen the personality of educators in facing educational challenges in the era of society 5.0